P42 Deprivation is associated with higher healthcare use in the salford lung study in asthma (SLS asthma). (December 2018) - Collier, S; Jones, R; Lay-Flurrie, J; Svedsater, H; Jacques, L; Bakerly, ND; Woodcock, A; Vestbo, J; Leather, DA
Abstract : Introduction/objectives: SLS asthma was a 12 month, open-label, randomised controlled trial in UK primary care that evaluated the clinical effectiveness of initiating fluticasone furoate/vilanterol (FF/VI) 100[200]/25 mcg versus continuing usual care (UC) in patients with symptomatic asthma. 1 In this post-hoc analysis, we assessed the effectiveness of FF/VI versus UC across different socioeconomic (deprivation) groups. Methods: Patient deprivation scores were derived by postcode using countrywide indices of deprivation and categorised into quintiles (Q1 [most deprived] to Q5 [least deprived]). Outcomes included percentage of Asthma Control Test (ACT) responders (patients achieving ACT total score ≥20 and/or increase from baseline ≥3) at Week 24 (primary endpoint) and at Weeks 12, 40 and 52, primary/secondary care contacts (PCC/SCC) and associated costs, treatment modifications, severe asthma exacerbations, and adherence to study medication (proportion of days covered). Analyses are descriptive only and were conducted without multiplicity adjustment. Results: 4218/4233 patients in the total population with available deprivation scores were included. In SLS asthma, patient distribution was homogeneous across the quintiles (˜20% each category), in contrast to SLS COPD (˜50% most deprived category). 2 At baseline, asthma patients in the more deprived categories were younger and more obese, and more likely smokers and to have uncontrolled asthma (ACT ≤15) with recent asthma symptoms, than in the less deprived categories. For FF/VI, the proportion of patients with ≥1 treatment modification during the study was relatively consistent across the quintiles (range: Q1 20%–Q5 24%); however, for UC, proportions were higher in the more deprived categories (range: Q1 26%–Q5 13%). Benefit for FF/VI over UC was seen in all deprivation quintiles for the percentage of ACT responders at Week 24 and at Weeks 12, 40, and 52. Greater deprivation was associated with higher rates of all-cause PCC/SCC regardless of treatment group (table 1). There was no consistent association between deprivation and annual exacerbation rates, adherence to study medication, or healthcare costs. Conclusions: In SLS asthma, greater deprivation was associated with higher rates of smoking, obesity, poorly controlled asthma and healthcare use. Initiating FF/VI was superior to continuing UC for the primary endpoint of ACT responders across all deprivation quintiles. Funding: GSK (HZA115150; NCT01706198 ). Please refer to page A266 for declarations of interest related to this abstract. References: Woodocock A, et al. Lancent 2017;390:2247–55. Jones R, et al. Thorax2017;72(Suppl 3):Abstract P27 (poster presented at the British Thoracic Society Winner Meting 2017)